Global cities, governance and diplomacy the urban link - Acuto, Michele 1984- (Routledge new diplomacy studies, 2013)
The book argues that looking at global cities can bring about three fundamental advantages on traditional IR paradigms. First, it facilitates an eclectic turn towards more nuanced analyses of world politics. Second, it widens the horizon of the discipline through a multiscalar image of global governance. Third, it underscores how global cities have a strategic diplomatic positioning when it comes to core contemporary challenges such as climate change.